Proanthocyanidins from Ginkgo biloba extract EGb 761® exert antioxidative activity in vitro and antiamnesic activity in vivo - Sens-Albert, Carla; Schmitt, Markus; Luderer, Gabriele; König, Beatrix C.; Melcher, Silas F.; Schneider, Heike; Kaiser, Simone; Tremmel, Sabine; Weisenburger, Sabrina; Kulić, Žarko; Lehner, Martin D. (Frontiers in Pharmacology, 2025)
IntroductionExtracts from Ginkgo biloba leaves are widely used in the treatment of age-related cognitive decline. As regulated herbal medicinal products, these extracts are adjusted to defined contents of flavonoids and terpene lactones, which are recognized as the active constituents. Recently, proanthocyanidins (PACs) have gained increasing interest as an additional constituent group with a yet undefined role in therapeutic activity. Notably, the PAC content exhibits substantial variability across ginkgo preparations, highlighting the need for further investigation into their pharmacological relevance.MethodsIn the present study, we used in vitro and in vivo assays combined with LC-(HR)-MS/MS metabolite profiling to assess the pharmacological activity, oral bioavailability, and metabolism of PACs isolated from G. biloba extract EGb 761®.ResultsGinkgo PACs concentration dependently reduced the basal cellular production of reactive oxygen species (ROS) in the rat neuronal cell line RN46A with higher potency than the ginkgo extract EGb 761® itself (IC50 = 0.97 μg/mL vs. 3.32 μg/mL). In a T-maze model, which assessed the working memory of mice, oral pretreatment with PACs and EGb 761® attenuated scopolamine-induced memory impairment with similar potency and efficacy (PAC ID50rel = 30 mg/kg, Imax = 69%; EGb 761® ID50rel = 39 mg/kg, Imax = 68%). Gallic acid metabolites derived from PACs were detected in the plasma and urine 1 h post administration, whereas microbiota-generated metabolites of PACs were only found at later time points (6 h). The pharmacodynamic activity in the T-maze model was most prominent at 1 h post administration, indicating that the microbiota-generated metabolites did not mediate the observed pharmacological effect. Comparison of two G. biloba products compliant with regulatory specifications for terpene lactones and flavonoids but differing in the PAC content—high (5.0%) vs. low (0.6%)—revealed superior activity for the high-PAC formulation both in the in vitro ROS assay (IC50 = 2.54 μg/mL vs. 9.01 μg/mL) and the in vivo model (63% vs. 34% reversal at 50 mg/kg).ConclusionA PAC fraction isolated from EGb 761® demonstrated antioxidative activity in vitro and antiamnesic effects in vivo. These findings support the hypothesis that PACs contribute to the efficacy of EGb 761®.